2015
DOI: 10.1080/00958972.2015.1062480
|View full text |Cite
|
Sign up to set email alerts
|

A new ruthenium cyclopentadienyl azole compound with activity on tumor cell lines and trypanosomatid parasites

Abstract: 2015): A new ruthenium cyclopentadienyl azole compound with activity on tumor cell lines and trypanosomatid parasites, Journal of Coordination Chemistry, As part of our efforts to develop organometallic ruthenium compounds bearing activity on both trypanosomatid parasites and tumor cells, a new Ru(II)-cyclopentadienyl clotrimazole complex, [RuCp(PPh 3 ) 2 (CTZ)](CF 3 SO 3 ) where Cp = cyclopentadienyl, CTZ = clotrimazole, was synthesized and characterized. The compound was evaluated in vitro on T. cruzi (Y str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Table 4 shows the structure-activity on several tumor cell lines of different ruthenium complexes. [114][115][116][117][118][119][120][121][122][123][124][125][126][127].…”
Section: Rapta Compoundsmentioning
confidence: 99%
“…Table 4 shows the structure-activity on several tumor cell lines of different ruthenium complexes. [114][115][116][117][118][119][120][121][122][123][124][125][126][127].…”
Section: Rapta Compoundsmentioning
confidence: 99%
“…Coordination of cyclopentadienyl Ru moiety with CTZ drug and PPh 3 ligand resulted in complex 21f with dual antiparasitic and anticancer activities. It was found that 21f exhibited higher in vitro toxicity against T. cruzi than the well-known antiparasitic drug nifurtimox and better cytotoxicity than cisplatin in ovary, breast, and cervix cancer cells . The sterol biosynthesis inhibitory action in T. cruzi and DNA interaction of complex were examined to gain insight into the putative “dual” mechanism of antiparasitic activity.…”
Section: Half-sandwich Ru(arene) Complexes With Clinically Used Drugsmentioning
confidence: 99%
“…It was found that 21f exhibited higher in vitro toxicity against T. cruzi than the well-known antiparasitic drug nifurtimox and better cytotoxicity than cisplatin in ovary, breast, and cervix cancer cells. 88 The sterol biosynthesis inhibitory action in T. cruzi and DNA interaction of complex were examined to gain insight into the putative "dual" mechanism of antiparasitic activity. The results showed that complex 21f had an impact on the biochemical mechanism of converting squalene to squalene oxide, despite the fact that it possessed weak interaction with DNA.…”
Section: Ru(arene) Complexes Of Carboxylate Nsaidsmentioning
confidence: 99%
“…These promising results triggered the research of several groups around the world on metal compounds of these azole monodentate ligands. 13,14,18,39,40 Additionally, related Mn(I) tricarbonyls with some of the selected ligands have been successfully developed and tested on other trypanosomatid parasites and more recently on bacteria. 41,42 In summary, five new fac-[Re(CO) 3 (NN)(CTZ)](PF 6 ) compounds, with the NN shown in Fig.…”
Section: Papermentioning
confidence: 99%